Austenitic stainless steel sheet and method for producing same
Patent Information
- Application Number
- JP2021058550
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-03-30
AI Technical Summary
【0012】 本発明の一態様によれば、厚さが一定程度以上あるにも関わらず、高強度かつ非磁性で安価なオーステナイト系ステンレス鋼を実現することができる。
Smart Images

Figure 0007634404000006 
Figure 0007634404000001 
Figure 0007634404000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel and a method for producing the same. [Background technology]
[0002] There is a high demand for small, lightweight, and stylish portable electronic devices, such as smartphones. Therefore, in the manufacture of metal exterior components for such portable electronic devices, a method of forming by cutting after cold forging under harsh conditions has come to be widely used in order to accommodate processing into complex shapes. Furthermore, depending on the design of the portable electronic device, mirror polishing may be performed after cutting. Here, the exterior components of portable electronic devices are not only required to be nonmagnetic to avoid adverse effects on geomagnetic sensors and the like built into the device, but also to have high strength. In addition, since the electronic devices are portable and often used in outdoor environments, the exterior components are also required to have higher corrosion resistance than electronic device components intended for indoor use.
[0003] Known metallic materials used in the manufacture of the above-mentioned exterior members include non-magnetic austenitic stainless steel plates (hereinafter simply referred to as "stainless steel plates") that are precipitation hardened stainless steels with a plate thickness of 1 mm to 8 mm and are made into non-magnetic members by cold forging and cutting (see, for example, Patent Document 1). Also known metallic materials include (austenite + ferrite) duplex stainless steels with a plate thickness of 5 mm or more (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-109215 A [Patent Document 2] JP 2017-155317 A Summary of the Invention [Problem to be solved by the invention]
[0005] The stainless steel sheet manufacturing method described in Patent Document 1 is a method capable of producing non-magnetic, high-strength parts, but has problems in that the manufacturing process is complicated and costly, and it may be difficult to apply depending on the product shape.
[0006] It is also known that cold rolling (temper rolling) is generally used to increase the strength of austenitic stainless steel, but cold rolling tends to result in a thin plate, making it difficult to produce austenitic stainless steel with a certain or greater plate thickness using a manufacturing method that includes cold rolling.
[0007] On the other hand, with precipitation hardening stainless steel and (austenite + ferrite) duplex stainless steel, it is possible to manufacture materials with a thickness of 3 mm to 10 mm that have a relatively uniform hardness in the thickness direction. However, martensitic stainless steel and precipitation hardening stainless steel have low corrosion resistance and are not suitable for use in highly corrosive environments. In addition, (austenite + ferrite) duplex stainless steel has excellent corrosion resistance, but its hardness is about 250 HV, making it unsuitable for strengths greater than that. In addition, both of these contain martensite and ferrite phases, which are ferromagnetic, so they may not be able to meet the needs of non-magnetic materials.
[0008] Furthermore, austenitic stainless steels containing large amounts of Ni and Mo are used as metallic exterior members for portable electronic devices, but the cost of such alloys tends to be high.
[0009] An object of one aspect of the present invention is to realize an austenitic stainless steel that is high-strength, non-magnetic, and inexpensive, despite having a certain degree of thickness or more. [Means for solving the problem]
[0010] In order to achieve the above object, an austenitic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.003% or more and 0.120% or less, Si: 2.0% or less, Mn: 2.0% or more and 15.0% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% or more and 9.0% or less, Mo: 0.01% or more and 3.00% or less, Cu: 0.01% or more and 5.0% or less, Cr: 14.0% or more and 22.0% or less, N: 0.005% or more and 0.400% or less, with the balance being Fe and unavoidable impurities, The following formula (1): A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) (wherein each element represents the content (mass%) of each element) is 0 or less, and The following formula (2): B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2) (wherein the element symbols represent the content (mass%) of each element) has a composition in which the value of B is -20 or less, The average hardness of the cross section parallel to the thickness direction is 250HV or more. The relative magnetic permeability μ is 1.1 or less, The thickness is 3mm or more.
[0011] In order to solve the above-mentioned problems, a method for producing an austenitic stainless steel according to one embodiment of the present invention comprises the following: C: 0.003% or more and 0.120% or less, Si: 2.0% or less, Mn: 2.0% or more and 15.0% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% or more and 9.0% or less, Cu: 0.01% or more and 5.0% or less, Cr: 14.0% or more and 22.0% or less, N: 0.005% or more and 0.400% or less, with the balance being Fe and unavoidable impurities; The following formula (1): A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) (wherein each element represents the content (mass%) of each element) is 0 or less, and The following formula (2): B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2) A rough hot rolling process in which a slab produced by casting has a chemical composition in which the value of B represented by the formula (wherein the element symbols represent the content (mass%) of each element) is -20 or less, is heated to a temperature of 1000°C or more and 1300°C or less, and then is subjected to rough hot rolling; A finish hot rolling process in which the steel strip obtained by the rough hot rolling process is subjected to finish hot rolling; A temper rolling process for temper rolling the steel strip at a temperature of less than 750 ° C after the finish hot rolling process, In the finish hot rolling process, The total rolling ratio of the finish hot rolling is 40% or more, The temperature of the finish hot rolling is 600°C or more and 1100°C or less, In the temper rolling process, The steel strip is subjected to temper rolling with a total rolling reduction ratio of 0.1% to 15%. Effect of the Invention
[0012] According to one aspect of the present invention, it is possible to realize an austenitic stainless steel that is high-strength, non-magnetic, and inexpensive, despite having a certain degree of thickness or more. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a process diagram showing the flow of each process in a method for producing an austenitic stainless steel according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the present invention will be described in detail below. Note that the following description is for the purpose of better understanding the gist of the invention, and does not limit the present invention unless otherwise specified. In this specification, the concentration of components is expressed in mass% unless otherwise specified.
[0015] [Points and Objects of the Invention] Key features of the present invention include the following (i) and (ii).
[0016] (i) Despite having a certain thickness (3 mm or more), the average hardness of the cross section parallel to the thickness direction is 250 HV or more, and the austenitic stainless steel has excellent non-magnetic properties.
[0017] (ii) The rolling strains of both hot rolling and cold rolling are added together to obtain the desired strength, specifically, the total rolling reduction in the finish hot rolling is 40% or more, and the temperature in the finish hot rolling is 600°C or more and 1100°C or less. If the final pass temperature in the finish hot rolling is 750°C or more, the steel strip after the finish hot rolling is cooled to 750°C or less at a cooling rate of 5°C / s or more. Furthermore, if necessary, oxide scale formed in the hot rolling process is removed, and then temper rolling is performed with a total rolling reduction of 0.1% or more and 15% or less. It has been discovered that the austenitic stainless steel described in (i) above can be obtained by a manufacturing method including these steps.
[0018] In an embodiment of the present invention, it is possible to realize an austenitic stainless steel and a manufacturing method thereof that enable structural components of electronic devices such as smartphones to be manufactured by cutting, etching, electric discharge machining, or the like, without complex forging processes.
[0019] The Vickers hardness of the austenitic stainless steel according to the embodiment of the present invention is 250 HV or more, which has the following advantages: In this embodiment, the Vickers hardness is expressed as the average value of the hardness of a cross section parallel to the thickness direction of the austenitic stainless steel.
[0020] Structural members of electronic devices such as smartphones are generally manufactured by cold forging and cutting. Steel generally undergoes work hardening, which increases the strength of the steel as it is processed. However, the degree of processing in cold forging is not uniform and varies depending on the part, so soft parts may remain. If soft parts remain in the steel, the surface is easily scratched, and the value of the product is reduced. When the austenitic stainless steel according to one embodiment of the present invention is applied as the structural member, the average hardness of the cross section parallel to the thickness direction is 250HV or more, so that no soft parts remain and the quality of the product is stabilized.
[0021] In addition, the "austenitic stainless steel" described in this specification includes both an austenitic stainless steel strip and an austenitic stainless steel plate. In other words, the present invention is applicable to both an austenitic stainless steel strip and an austenitic stainless steel plate.
[0022] An object of the present invention is to provide an austenitic stainless steel having high strength and excellent non-magnetic properties, and a manufacturing method thereof. By using such an austenitic stainless steel, structural members of electronic devices such as smartphones can be manufactured by cutting, etching, electric discharge machining, etc., without complex forging.
[0023] [Method of manufacturing austenitic stainless steel] As shown in FIG. 1, an austenitic stainless steel according to one embodiment of the present invention can be produced by carrying out the steps of steelmaking, rough hot rolling, finish hot rolling, cooling, and temper rolling.
[0024] More specifically, first, molten steel is obtained using a general steelmaking method, and then a slab is produced by casting (steelmaking process). The slab produced by casting has a chemical composition shown in the "Chemical composition of austenitic stainless steel" described below.
[0025] Furthermore, in this embodiment, the slab produced by casting is heated to a temperature of 1000°C or more and 1300°C or less, and then the slab is subjected to rough hot rolling (rough hot rolling process). The steel strip obtained by the rough hot rolling process is subjected to finish hot rolling (finish hot rolling process). The steel strip after the finish hot rolling process is cooled as necessary (cooling process). The steel strip that has been sufficiently cooled after the finish hot rolling process is subjected to temper rolling (temper rolling process).
[0026] In the finish hot rolling step, the total rolling ratio of the finish hot rolling is 40% or more, and the temperature of the finish hot rolling is 600°C or more and 1100°C or less.
[0027] In the cooling step, when the final pass temperature of the steel strip in the finish hot rolling step is 750°C or higher, the steel strip is cooled to 750°C or lower at a cooling rate of 5°C / s or higher prior to the temper rolling step. When the final pass temperature of the steel strip in the finish hot rolling step is lower than 750°C, the cooling step does not need to be performed.
[0028] Furthermore, the obtained austenitic stainless steel may be subjected to pickling treatment as necessary in order to remove oxide scale formed in the hot rolling process (pickling process). Generally, the pickling treatment is carried out in an annealing and pickling line in which the annealing process and the pickling process are connected. When carrying out the pickling treatment, heat may be applied to the austenitic stainless steel within a temperature range in which the hardness of the austenitic stainless steel does not decrease (specifically, 900°C or less).
[0029] Thereafter, if necessary, oxide scale formed in the hot rolling process is removed, and then temper rolling is performed with a total rolling reduction ratio of 0.1% to 15% (temper rolling process). By satisfying the above conditions at least in the finish hot rolling process and the temper rolling process, it is possible to obtain an austenitic stainless steel having a desired hardness in a cross section parallel to the thickness direction.
[0030] According to the above steps, it is possible to provide an austenitic stainless steel that has an average hardness of 250 HV or more in a cross section parallel to the thickness direction, despite having a thickness of 3 mm or more, and that has excellent non-magnetic properties.
[0031] The "average hardness of a cross section parallel to the thickness direction" refers to the average value of the results of measuring Vickers hardness at multiple points in different positions in the thickness direction with a load of 1 kg so that the variation in hardness at each measurement position can be seen for the cross section parallel to the thickness direction. For example, if measurements are taken at 10 points each at the very surface layer of the plate thickness, at the 1 / 8 position, the 1 / 4 position, and the 1 / 2 position of the plate thickness, the "average hardness of a cross section parallel to the thickness direction" means the average value of these 40 points in total. Vickers hardness can be measured, for example, by a method conforming to Japanese Industrial Standards (JIS) Z2244:2009.
[0032] (relative permeability) In characterizing austenitic stainless steel, the relative magnetic permeability μ is generally preferably 1.1 or less, more preferably 1.05 or less. In this specification, the relative magnetic permeability is the ratio of the magnetic permeability of austenitic stainless steel to the magnetic permeability of air.
[0033] In the austenitic stainless steel with the chemical composition adjusted as described above, no processing-induced martensite phase is generated in the normal steel plate manufacturing process and the subsequent cold forging process. Therefore, magnetization due to the processing-induced martensite phase can be avoided. However, when the slab is melted, a δ ferrite phase may be generated at high temperatures, and if the δ ferrite phase remains, non-magnetic properties with a relative permeability μ of 1.1 or less may not be obtained. In addition, if the δ ferrite phase is mixed as a different phase in the austenitic stainless steel product, the appearance of the mirror-polished product may be impaired. Therefore, it is necessary that the δ ferrite phase is sufficiently eliminated at the stage of the steel plate, which is the material to be subjected to cold forging. In this regard, in the manufacturing method according to one embodiment of the present invention, the amount of δ ferrite phase generated during the melting of the slab is suppressed in the austenitic stainless steel with the chemical composition adjusted as described above. Since the δ ferrite phase is ferromagnetic, its presence or absence can be evaluated by the relative permeability μ.
[0034] (Target characteristics) In the embodiment of the present invention, the average hardness of the cross section parallel to the thickness direction of the austenitic stainless steel is targeted to be 250HV or more (SUS304CSP-1 / 2H standard). In addition, the thickness of the austenitic stainless steel is targeted to be 3mm or more, since the thickness range of SUS301CSP of Tokushu Kinzoku Excel is about 2.5mm or less.
[0035] (Total reduction ratio of finishing hot rolling) The total rolling ratio of the finish hot rolling is preferably 40% or more. If the total rolling ratio of the finish hot rolling is less than 40%, the rolling strain in the hot rolling is not sufficient, and even if the rolling strain is applied in the subsequent temper rolling, it is difficult to obtain the target hardness. Although it is possible to obtain the target hardness by applying a temper rolling ratio more than necessary, it becomes difficult to secure a plate thickness of 3 mm or more as the temper rolling ratio increases, and this leads to a decrease in productivity and an increase in cost. Note that, when the thickness of the steel strip before the finish hot rolling process is h1 and the thickness of the steel strip after the finish hot rolling process is h2, the relational expression of total rolling ratio = (h1-h2) / h1 is established.
[0036] The total rolling reduction ratio of the finish hot rolling can be appropriately determined according to the final desired thickness of the austenitic stainless steel, and the higher the reduction ratio, the thinner the final thickness tends to be. The total rolling reduction ratio of the finish hot rolling cannot be generally determined because it can be adjusted by rolling in other processes, but from the viewpoint of realizing the above-mentioned thickness of 3 mm or more, it may be 99% or less.
[0037] (Finishing hot rolling temperature) The finish hot rolling temperature is preferably 600°C or higher and 1100°C or lower. If the finish hot rolling temperature and the final pass rolling temperature are lower than 600°C, the amount of rolling strain imparted to the surface layer of the steel strip will be larger than that of the central portion in the thickness direction, and there is a possibility that the strength will not be sufficiently increased in some parts. On the other hand, if the finish hot rolling temperature is higher than 1100°C, the rolling strain will become the driving force for recrystallization, and recrystallization will occur immediately after rolling, and the desired hardness may not be obtained.
[0038] In the temper rolling process in this embodiment, it is preferable to carry out temper rolling at a total rolling reduction of 0.1% or more and 15% or less. Since the desired hardness cannot be stably obtained only with the rolling strain introduced under the above-mentioned hot rolling conditions, it is necessary to introduce additional rolling strain in temper rolling in addition to the rolling strain introduced in hot rolling. On the other hand, in consideration of equipment specifications, productivity reduction, and cost increase, there is a limit to the total rolling reduction that can actually be imparted by temper rolling. Therefore, although it depends on the hot rolling conditions, it is preferable to carry out temper rolling so that the total rolling reduction is 0.1% or more and 15% or less, preferably 10% or more. By such a temper rolling process, it is possible to suppress and sufficiently reduce the generation of the above-mentioned deformation-induced martensite phase.
[0039] In this embodiment, the steel strip having a temperature of less than 750°C after the finish hot rolling process is subjected to temper rolling. When the final pass temperature of the steel strip in the finish hot rolling process is less than 750°C, it is possible to perform the temper rolling process without other processes such as a cooling process. In this case, the total rolling reduction ratio in the temper rolling process can be set relatively low, and may be appropriately determined, for example, from the viewpoint of making the final thickness of the austenitic stainless steel a desired thickness, within the range of 0.1 to 10%. By performing the temper rolling process directly from the finish hot rolling process, the Vickers hardness of the austenitic stainless steel tends to be further increased, or the relative magnetic permeability of the austenitic stainless steel tends to be further reduced.
[0040] (cooling process) After the above-mentioned finish hot rolling step, it is preferable to include a cooling step in which the steel strip subjected to finish hot rolling is cooled to 750°C or less at a cooling rate of 5°C / s or more when the final pass temperature of the finish hot rolling is 750°C or more. The rolling strain accumulated in the hot rolled material by the finish hot rolling decreases immediately after the finish hot rolling if the material is kept at a high temperature. In order to retain a level of rolling strain preferable for increasing strength, it is preferable to quickly cool the steel strip after the finish hot rolling to a temperature range where no significant reduction in rolling strain occurs.
[0041] The final temperature of the steel strip in the cooling step is preferably 400° C. or higher from the viewpoint of performing subsequent treatments such as temper rolling sufficiently and smoothly. Also, the cooling rate in the cooling step is preferably 80° C. / s or lower from the viewpoint of productivity.
[0042] In this embodiment, when the steel strip after the finish hot rolling is cooled in the cooling process and then subjected to the temper rolling process, the total rolling reduction in the temper rolling process can be set relatively high. In this case, for example, from the viewpoint of making the final thickness of the austenitic stainless steel a desired thickness, the total rolling reduction in the temper rolling process is preferably 5.0% or more, and more preferably 10% or more.
[0043] In the embodiment of the present invention, other steps may be further included in addition to the above-mentioned finish hot rolling step, temper rolling step, and cooling step, so long as the effects of the present embodiment can be obtained. As the other steps, various steps known in the production of austenitic stainless steels can be adopted, and the order of such other steps can be appropriately determined so long as the effects of the other steps can be obtained in addition to the effects of the present embodiment.
[0044] [Chemical composition of austenitic stainless steel] The chemical composition of an austenitic stainless steel according to one embodiment of the present invention is, in mass%, C: 0.003% or more and 0.120% or less, Si: 2.0% or less, Mn: 2.0% or more and 15.0% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% or more and 8.0% or less, Mo: 0.01% or more and 3.00% or less, Cu: 0.01% or more and 5.0% or less, Cr: 14.0% or more and 22.0% or less, N: 0.005% or more and 0.400% or less, with the balance being Fe and unavoidable impurities.
[0045] The chemical composition of an austenitic stainless steel according to one embodiment of the present invention has a composition in which the value of A shown in the following formula (1) is 0 or less, and the value of B shown in the following formula (2) is -20 or less. In each of the following formulas, the elements shown represent the content (mass%) of each element. A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2)
[0046] Equation (1) is a component regression equation relating to the magnetic index, and the A value obtained by equation (1) represents the degree of non-magnetism in the austenitic stainless steel of this embodiment. Here, in stainless steel, the austenite phase is non-magnetic, and the ferrite phase is magnetic. Although the austenitic stainless steel of this embodiment is inherently non-magnetic, some ferrite phase may be generated and dispersed during melting depending on the component blend, so that the austenitic stainless steel may have a property of being weakly magnetic. The A value represents the generation ratio of the ferrite phase (the aforementioned δ-ferrite phase) during melting. By having the A value of less than 0, it is possible to realize a relative magnetic permeability of less than 1.1. In this embodiment, the lower the A value, the better from the viewpoint of realizing the non-magnetism of the austenitic stainless steel, but from the viewpoint of realizing a chemical composition that exhibits the desired physical properties, for example, it is preferable to set the A value to -25 It may be more than that.
[0047] Equation (2) is a component regression equation for the magnetic index, and the B value obtained by equation (2) represents the degree of non-magnetism in the austenitic stainless steel of this embodiment. The austenitic stainless steel of this embodiment of the present invention has the property of being weakly magnetic, since a magnetic martensite phase (the above-mentioned processing-induced martensite phase) may be generated by cold rolling depending on the composition of elements. The B value represents the generation ratio of the processing-induced martensite phase during cold rolling. By having the B value of less than -20, it is possible to realize a relative permeability of less than 1.1. In this embodiment, the lower the B value, the better from the viewpoint of realizing the non-magnetism of the austenitic stainless steel, but for example, from the viewpoint of realizing a chemical composition that exhibits the desired physical properties, the B value may be -250 or more.
[0048] As described above, the Vickers hardness of the austenitic stainless steel in the embodiment of the present invention is 250 HV or more from the viewpoint of stabilizing the quality of products processed from the austenitic stainless steel. The Vickers hardness of the austenitic stainless steel in the embodiment may be appropriately determined depending on the application of the product or the mechanical properties required of the product, and cannot be generally stated, but may be 400 HV or less from the viewpoint of the workability of the product, for example.
[0049] As described above, the relative magnetic permeability μ of the austenitic stainless steel in the embodiment of the present invention is 1.1 or less from the viewpoint of meeting the needs of non-magnetic properties or from the viewpoint of surface workability such as mirror finishing. The relative magnetic permeability of the austenitic stainless steel in the present embodiment is desirably low from the above viewpoint, but can be appropriately determined within a range that can meet the needs of non-magnetic properties and may be 1.001 or more. The relative magnetic permeability can be measured by a known measuring device. In the present embodiment, the relative magnetic permeability tends to be smaller than the above-mentioned A value and B value, or by directly performing temper rolling after the above-mentioned finish rolling.
[0050] Furthermore, as described above, the thickness of the austenitic stainless steel in the embodiment of the present invention is 3 mm or more from the viewpoint of the use or processing of the product. The thickness of the austenitic stainless steel in the present embodiment can be appropriately determined from the range that can be realized by the above-mentioned manufacturing method of the austenitic stainless steel, depending on the requirements for the product or processing. From such a viewpoint, the thickness of the austenitic stainless steel in the present embodiment may be, for example, 15 mm or less.
[0051] An austenitic stainless steel according to one embodiment of the present invention may further contain, in addition to the above chemical composition, one or more of the following, by mass%, Al: 0.07% or less, O: 0.001% or more and 0.010% or less, V: 0.01% or more and 0.50% or less, B: 0.0003% or more and 0.0100% or less, and Ti: 0.0005% or more and 0.50% or less.
[0052] An austenitic stainless steel according to one embodiment of the present invention may further contain, in addition to the above chemical composition, one or more of the following, by mass%, Co: 0.01% or more and 0.50% or less, Zr: 0.01% or more and 0.10% or less, Nb: 0.01% or more and 0.10% or less, Mg: 0.0005% or more and 0.0030% or less, Ca: 0.0003% or more and 0.0030% or less, Y: 0.01% or more and 0.20% or less, REM (rare earth metals): 0.01% or more and 0.10% or less, Sn: 0.001% or more and 0.500% or less, Sb: 0.001% or more and 0.500% or less, Pb: 0.01% or more and 0.10% or less, and W: 0.01% or more and 0.50% or less.
[0053] Hereinafter, "%" in the chemical composition of the austenitic stainless steel means mass % unless otherwise specified.
[0054] C (carbon) is an interstitial element that contributes to high strength through work hardening and strain aging. C is also an austenite-forming element that stabilizes the austenite phase, and is effective in maintaining non-magnetic properties. It is preferable for austenitic stainless steel to have a C content of 0.003% or more. However, since excessive C content hardens austenitic stainless steel and reduces its cold forgeability, it is preferable to limit the C content to 0.12% or less.
[0055] Silicon (Si) is an element used as a deoxidizer for steel in the steelmaking process. In addition, silicon has the effect of improving age hardening in the stress relief heat treatment performed after cold forging. On the other hand, since silicon has a large solid solution strengthening effect and has the effect of reducing stacking fault energy and increasing work hardening, excessive silicon content is a factor that reduces cold forgeability. Therefore, it is preferable that the Si content is limited to 2.0% or less.
[0056] Mn (manganese) is an element that constitutes oxide-based inclusions as MnO. In addition, Mn has a small effect on solid solution strengthening, and is an austenite forming element that suppresses processing-induced martensitic transformation, so it is an effective element for ensuring cold forgeability and maintaining non-magnetic properties. Furthermore, it is an element that can be used as a substitute for Ni as an austenite forming element. It is desirable to add 2.0% or more to reduce Ni. However, excessive Mn content is a factor in reducing corrosion resistance. Therefore, it is preferable to limit the Mn content to 15.0% or less.
[0057] P (phosphorus) is an element that reduces corrosion resistance, and an excessive reduction in P content increases the steelmaking load, so the P content is preferably 0.04% or less.
[0058] S (sulfur) forms MnS, which deteriorates corrosion resistance, and excessive desulfurization increases the steelmaking load. Therefore, the S content is preferably limited to 0.03% or less.
[0059] Ni (nickel) is an element effective in improving corrosion resistance. In the austenitic stainless steel of this embodiment, the Ni content is preferably 0.5% or more, and more preferably 6.0% or more. Moreover, excessive Ni content increases material costs. Therefore, the Ni content is preferably limited to 9.0% or less.
[0060] Cr (chromium) is an element that improves corrosion resistance. In order to ensure corrosion resistance suitable for exterior members of portable electronic devices, it is preferable for austenitic stainless steel to have a Cr content of 14.0% or more. However, a large amount of Cr content can cause a decrease in cold forgeability. Therefore, it is preferable that the upper limit of the Cr content is limited to 22.0%.
[0061] N (nitrogen) is an interstitial element like C, and contributes to high strength through work hardening and strain aging. N also stabilizes the austenite phase and is effective in maintaining non-magnetic properties. It is preferable for austenitic stainless steel to have an N content of 0.005% or more. However, excessive N content hardens austenitic stainless steel and reduces cold forgeability. Therefore, it is preferable to limit the N content to 0.400% or less.
[0062] Mo (molybdenum) is an element that is effective in improving the corrosion resistance of austenitic stainless steel. In austenitic stainless steel, Mo is added as necessary after ensuring the above-mentioned Cr content, but adding a large amount of Mo increases costs, so if Mo is added, the Mo content is set to 0.01% or more and 3.00% or less.
[0063] It is known that Cu (copper) suppresses the work hardening of the austenite phase and is effective in improving cold forgeability. It is also known that Cu is an element that brings about age hardening in the heating temperature range of the stress relief heat treatment performed after cold forging. Furthermore, it is also an element that can be used as a substitute for Ni as an austenite forming element. As a result of various investigations, if Cu is contained, the Cu content is set to 0.01% or more and 5.0% or less.
[0064] Al (aluminum) has a higher oxygen affinity than Si and Mn, and when the Al content is 0.003% or more, coarse oxide-based inclusions that become the starting point of internal cracks during cold forging are likely to form. In addition, excessively low Al content is likely to increase costs. As a result of various investigations, when Al is contained, the Al content is preferably 0.07% or less, and more preferably 0.01% or less.
[0065] When the O (oxygen) content is low, Mn, Si, etc. are less likely to oxidize, and the ratio of Al2O3 in the inclusions increases. Also, when the O content is excessively high, coarse inclusions with particle sizes exceeding 5 μm are likely to form. As a result of various investigations, when O is contained, the O content is preferably 10 ppm (0.001%) or more, preferably 100 ppm (0.010%) or less, and more preferably 80 ppm (0.008%) or less.
[0066] V (vanadium) has the effect of enhancing the age hardening ability during heating in the stress relief heat treatment performed after cold forging. Although V has an age hardening effect, the inclusion of a large amount of V leads to an increase in costs. Therefore, when V is contained, the V content is preferably 0.01% or more and 0.50% or less.
[0067] Regarding B (boron), a large amount of B can cause a decrease in workability due to the formation of borides, so when B is contained, the B content is preferably 0.0003% or more and 0.0100% or less, and more preferably 0.0050% or less.
[0068] Ti (titanium) is a carbonitride forming element, fixes C and N, and suppresses the decrease in corrosion resistance caused by sensitization. Such an effect is exhibited when Ti is contained at 0.0005% or more. Therefore, when Ti is contained, the Ti content is preferably 0.0005% or more. On the other hand, when the Ti content exceeds 0.50%, Ti precipitates as carbides with non-uniform sizes and is unevenly localized in the steel, inhibiting regular recrystallized grain growth. In addition, since Ti is very expensive, it is preferable to set the upper limit of the Ti content to 0.50%.
[0069] Co (cobalt) has the effect of improving crevice corrosion resistance. On the other hand, excessive Co content hardens the austenitic stainless steel and adversely affects the bendability. Therefore, when Co is contained, the Co content is preferably 0.01% or more and 0.50% or less, more preferably 0.10% or less.
[0070] Zr (zirconium) is an element with high affinity for C and N, and precipitates as carbides or nitrides during hot rolling, reducing the amount of dissolved C and N in the matrix and improving workability. On the other hand, excessive Zr content hardens austenitic stainless steel and adversely affects bendability. Therefore, when Zr is contained, the Zr content is preferably 0.01% or more and 0.10% or less, more preferably 0.05% or less.
[0071] Niobium (Nb) is an element with high affinity for C and N, and precipitates as carbides or nitrides during hot rolling, reducing the amount of dissolved C and N in the matrix and improving workability. On the other hand, excessive Nb content hardens austenitic stainless steel and adversely affects bendability. Therefore, when Nb is contained, the Nb content is preferably 0.01% or more and 0.10% or less, more preferably 0.05% or less.
[0072] Magnesium (Mg) forms Mg oxide together with Al in molten steel and acts as a deoxidizer. On the other hand, excessive Mg content reduces the toughness of austenitic stainless steel and decreases manufacturability. Therefore, when Mg is contained, the Mg content is preferably 0.0005% or more and 0.0030% or less, more preferably 0.0020% or less.
[0073] Ca (calcium) is an element that improves hot workability. On the other hand, if an excessive amount of Ca is contained, the toughness of the austenitic stainless steel decreases, leading to a decrease in manufacturability, and furthermore, the corrosion resistance decreases due to the precipitation of CaS. Therefore, when Ca is contained, the Ca content is preferably 0.0003% or more and 0.0030% or less, more preferably 0.0020% or less.
[0074] Y (yttrium) is an element that reduces the viscosity decrease of molten steel and improves cleanliness. On the other hand, if Y is contained in excess, the effect is saturated and further, workability is reduced. Therefore, when Y is contained, the Y content is preferably 0.01% or more and 0.20% or less, more preferably 0.10% or less.
[0075] REM (rare earth metals: elements with atomic numbers 57 to 71, such as La, Ce, and Nd) are elements that improve high-temperature oxidation resistance. On the other hand, if REM is contained in excess, the effect is saturated, and furthermore, surface defects occur during hot rolling, reducing manufacturability. Therefore, when REM is contained, the REM content is preferably 0.01% or more and 0.10% or less, more preferably 0.05% or less.
[0076] Sn (tin) is effective in improving workability by promoting the formation of deformation bands during rolling. On the other hand, if excessive Sn is contained, the effect is saturated and workability is further reduced. Therefore, when Sn is contained, the Sn content is preferably 0.001% or more and 0.500% or less, more preferably 0.200% or less.
[0077] Sb (antimony) is effective in improving workability by promoting the formation of deformation bands during rolling. On the other hand, if Sb is contained in excess, the effect saturates and workability further deteriorates. Therefore, when Sb is contained, the Sb content is preferably 0.001% or more and 0.500% or less, more preferably 0.200% or less.
[0078] Pb (lead) lowers the melting point of the grain boundary and reduces the bonding strength of the grain boundary, which may lead to deterioration of hot workability, such as liquation cracking due to grain boundary melting. Therefore, if Pb is contained, the Pb content is preferably 0.01% or more and 0.10% or less.
[0079] W (tungsten) has the effect of improving high-temperature strength without impairing ductility at room temperature. However, excessive addition of W generates coarse eutectic carbides, which causes a decrease in ductility, so if W is contained, the W content is preferably 0.01% or more and 0.50% or less.
[0080] [Additional Notes] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in the different embodiments are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment.
[0081] 〔summary〕 As is clear from the above description, the austenitic stainless steel in the embodiment of the present invention contains, by mass%, C: 0.003% to 0.120%, Si: 2.0% or less, Mn: 2.0 to 15.0%, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% to 8.0%, Mo: 0.01% to 3.00% or less, Cu: 0.01% to 5.0% or less, Cr: 14.0% to 22.0% or less, N: 0.005% to 0.400% or less, with the balance being Fe and unavoidable impurities, and has a composition in which the value of A represented by the following formula (1) is 0 or less and the value of B represented by the following formula (2) is -20 or less, the average hardness of a cross section parallel to the thickness direction is 250 HV or more, the relative permeability μ is 1.1 or less, and the thickness is 3 mm or more. A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) (In the formula, the elements listed represent the content (mass%) of each element.) B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2) (In the formula, the element symbols represent the content (mass%) of each element.)
[0082] In addition, a method for producing an austenitic stainless steel in an embodiment of the present invention includes a rough hot rolling process in which a slab produced by casting and having the above-mentioned chemical composition is heated to a temperature of 1000°C or more and 1300°C or less, and then rough hot rolling is performed, a finish hot rolling process in which finish hot rolling is performed on the steel strip obtained by the rough hot rolling process, and a temper rolling process in which the steel strip after the finish hot rolling process at a temperature of less than 750°C is temper rolled, wherein in the finish hot rolling process, a total rolling reduction ratio of the finish hot rolling is 40% or more, and the finish hot rolling temperature is 600°C or more and 1100°C or less, and in the temper rolling process, the steel strip is temper rolled at a total rolling reduction ratio of 0.1% or more and 15% or less.
[0083] Therefore, according to the embodiment of the present invention, it is possible to realize an austenitic stainless steel that is high in strength, non-magnetic, and inexpensive, even though it has a certain degree of thickness or more.
[0084] In an embodiment of the present invention, the above composition may further include, by mass%, one or more of Al: 0.07% or less, O: 0.001% to 0.010%, V: 0.01% to 0.50%, B: 0.0003% to 0.0100%, and Ti: 0.0005% to 0.50%. This configuration is even more effective in terms of further exerting the effects of these elements.
[0085] In addition, in an embodiment of the present invention, the above composition may further include, in mass%, one or more of Co: 0.01% to 0.50%, Zr: 0.01% to 0.10%, Nb: 0.01% to 0.10%, Mg: 0.0005% to 0.0030%, Ca: 0.0003% to 0.0030%, Y: 0.01% to 0.20%, REM (rare earth metal): 0.01% to 0.10%, Sn: 0.001% to 0.500%, Sb: 0.001% to 0.500%, Pb: 0.01% to 0.10%, and W: 0.01% to 0.50%. This configuration is even more effective in terms of further exerting the effects of these elements.
[0086] In an embodiment of the present invention, when the final pass temperature of the steel strip in the finish hot rolling step is 750°C or higher, the method may further include a cooling step of cooling the steel strip to less than 750°C at a cooling rate of 5°C / s or higher prior to the temper rolling step. This configuration is even more effective from the viewpoint of suppressing the occurrence of rolling strain.
[0087] Alternatively, in an embodiment of the present invention, the temper rolling step may be a step of subjecting a steel strip, whose final pass temperature in the finish hot rolling step is less than 750° C., to temper rolling at a total rolling reduction ratio of 0.1% to 10%. This configuration is even more effective from the viewpoint of increasing the hardness and non-magnetic properties of the austenitic stainless steel. EXAMPLES
[0088] Slabs A1 to A7, B1 and B2 were prepared. The chemical composition, A value and B value of each slab are shown in Table 1. Table 1 shows the chemical composition of the slabs. In Table 1, the value of each element represents the mass% of each component contained in the austenitic stainless steel. The remainder of the chemical composition of the slab is Fe and unavoidable impurities. In Table 1, the A value is the value calculated from the above-mentioned formula (1), and the B value is the value calculated from the above-mentioned formula (2).
[0089] [Table 1]
[0090] Using the above slab, austenitic stainless steel steel plates 1 to 36 were manufactured by the method shown in FIG. 1 described above. Various conditions in the manufacturing method of steel plates 1 to 36 are shown in Tables 2 and 3. In Tables 2 and 3, "plate thickness A" is the thickness of the plate-shaped slab before the rough hot rolling process, and "plate thickness B" is the thickness of the plate-shaped steel plate after the rough hot rolling process. Furthermore, "final temperature" is the temperature of the steel plate when rolling is performed in the final pass of the finish rolling process. Furthermore, "final temperature" is the temperature of the steel plate immediately after the cooling process.
[0091] [Table 2]
[0092] [Table 3]
[0093] Tables 4 and 5 show the plate thickness, Vickers hardness and relative magnetic permeability of the austenitic stainless steel plates 1 to 36 manufactured using each of the above slabs. In Tables 4 and 5, "finished plate thickness" refers to the thickness of the steel plate after the temper rolling process, and "Vickers hardness" refers to the average value of the results of measuring the Vickers hardness of the cross section parallel to the thickness direction of the steel plate at 10 points (40 points in total) at the extreme surface layer of the plate thickness, the 1 / 8 position of the plate thickness, the 1 / 4 position of the plate thickness, and the 1 / 2 position of the plate thickness, under a load of 1 kg. The Vickers hardness was measured by a method conforming to JIS Z2244:2009. In Tables 4 and 5, the relative magnetic permeability refers to the average value of the results of measuring three points on the cross section parallel to the thickness direction of the steel plate using a relative magnetic permeability measuring device. In addition, in Table 5, "※1" indicates that deformation-induced martensite was formed, and "※2" indicates that δ-ferrite was formed during melting.
[0094] [Table 4]
[0095] [Table 5]
[0096] As is clear from Tables 1 to 5, the average Vickers hardness of the cross section parallel to the thickness direction of the austenitic stainless steels manufactured by the manufacturing method satisfying the conditions of the manufacturing method according to one embodiment of the present invention was 250 HV or more in all cases, the relative permeability was sufficiently low, and the finished plate thickness was sufficiently thick.
[0097] On the other hand, the austenitic stainless steels manufactured by methods not satisfying the above manufacturing conditions all had sufficient finished plate thickness. However, the average hardness of the cross section parallel to the thickness direction of steel plates 30 to 34 was less than 250 HV. Moreover, steel plates 35 and 36 all had a relative magnetic permeability higher than 1.1. [Industrial Applicability]
[0098] The present invention can be used for austenitic stainless steel strips and the like that are suitable for applications requiring relatively thick, high-strength stainless steel, such as structural components for electronic devices such as smartphones, steel belts, press plates, and the like.
Claims
1. The steel sheet contains, in mass %, C: 0.003% or more and 0.120% or less, Si: 2.0% or less, Mn: 2.0% or more and 15.0% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% or more and 9.0% or less, Mo: 0.01% or more and 3.00% or less, Cu: 0.01% or more and 5.0% or less, Cr: 14.0% or more and 22.0% or less, N: 0.005% or more and 0.400% or less, Co: 0.01% or more and 0.50% or less, with the balance being Fe and unavoidable impurities, The following formula (1): A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) (wherein each element symbol represents the content (mass%) of each element) is 0 or less, and The following formula (2): B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2) (wherein the element symbols represent the contents (mass%) of each element) in which the value of B is −20 or less, The average hardness of a cross section parallel to the thickness direction is 250 HV or more, The relative magnetic permeability μ is 1.1 or less, An austenitic stainless steel plate having a thickness of 3 mm or more.
2. 2. The austenitic stainless steel sheet according to claim 1, further containing, by mass%, one or more of Al: 0.07% or less, O: 0.001% or more and 0.010% or less, V: 0.01% or more and 0.50% or less, B: 0.0003% or more and 0.0100% or less, and Ti: 0.0005% or more and 0.50% or less.
3. 3. The austenitic stainless steel sheet according to claim 1 or 2, further containing, by mass%, one or more of Zr: 0.01% or more and 0.10% or less, Nb: 0.01% or more and 0.10% or less, Mg: 0.0005% or more and 0.0030% or less, Ca: 0.0003% or more and 0.0030% or less, Y: 0.01% or more and 0.20% or less, REM (rare earth metal): 0.01% or more and 0.10% or less, Sn: 0.001% or more and 0.500% or less, Sb: 0.001% or more and 0.500% or less, Pb: 0.01% or more and 0.10% or less, and W: 0.01% or more and 0.50% or less.
4. The steel sheet contains, in mass %, C: 0.003% or more and 0.120% or less, Si: 2.0% or less, Mn: 2.0% or more and 15.0% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.5% or more and 9.0% or less, Mo: 0.01% or more and 3.00% or less, Cu: 0.01% or more and 5.0% or less, Cr: 14.0% or more and 22.0% or less, N: 0.005% or more and 0.400% or less, Co: 0.01% or more and 0.50% or less, with the balance being Fe and unavoidable impurities, The following formula (1): A=3(Cr+Mo)+4.5Si-2.8Ni-1.4(Mn+Cu)-84(C+N)-19.8...(1) (wherein each element symbol represents the content (mass%) of each element) is 0 or less, and The following formula (2): B=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo...(2) (wherein the element symbols represent the content (mass%) of each element) A slab produced by casting has a chemical composition in which the value of B is -20 or less. A rough hot rolling process in which the slab is heated to a temperature of 1000 ° C. or more and 1300 ° C. or less and then subjected to rough hot rolling; A finish hot rolling process in which the steel strip obtained by the rough hot rolling process is subjected to finish hot rolling; A temper rolling process for temper rolling the steel strip at a temperature of less than 750 °C after the finish hot rolling process, In the finish hot rolling process, The total rolling ratio of the finish hot rolling is 40% or more, The temperature of the finish hot rolling is 600° C. or more and 1100° C. or less, In the temper rolling process, The steel strip is subjected to temper rolling with a total rolling ratio of 0.1% to 15%. A method for producing an austenitic stainless steel sheet, the method comprising the steps of: producing an austenitic stainless steel sheet having an average hardness of 250 HV or more in a cross section parallel to the thickness direction, a relative magnetic permeability μ of 1.1 or less, and a thickness of 3 mm or more.
5. 5. The method for producing an austenitic stainless steel sheet according to claim 4, further comprising a cooling step of cooling the steel strip to less than 750°C at a cooling rate of 5°C / s or more prior to the temper rolling step when a final pass temperature of the steel strip in the finish hot rolling step is 750°C or more.
6. 5. The method for producing an austenitic stainless steel sheet according to claim 4, wherein the temper rolling step is a step of subjecting the steel strip to temper rolling at a total rolling reduction ratio of 0.1% or more and 10% or less, the steel strip having a final pass temperature of less than 750°C in the finish hot rolling step.
7. The method for producing an austenitic stainless steel sheet according to any one of claims 4 to 6, wherein the slab further contains, by mass%, one or more of Al: 0.07% or less, O: 0.001% or more and 0.010% or less, V: 0.01% or more and 0.50% or less, B: 0.0003% or more and 0.0100% or less, and Ti: 0.0005% or more and 0.50% or less.
8. The method for producing an austenitic stainless steel sheet according to any one of claims 4 to 7, wherein the slab further contains, by mass%, one or more of Zr: 0.01% or more and 0.10% or less, Nb: 0.01% or more and 0.10% or less, Mg: 0.0005% or more and 0.0030% or less, Ca: 0.0003% or more and 0.0030% or less, Y: 0.01% or more and 0.20% or less, REM (rare earth metal): 0.01% or more and 0.10% or less, Sn: 0.001% or more and 0.500% or less, Sb: 0.001% or more and 0.500% or less, Pb: 0.01% or more and 0.10% or less, and W: 0.01% or more and 0.50% or less.
Citation Information
Patent Citations
Nonmagnetic stainless steel excellent in surface property and production thereof
JP1995113144A
Precipitation curing type martensitic stainless steel sheet for steel belt and manufacturing method
JP2017155317A
Nonmagnetic austenitic stainless steel sheet and method for producing nonmagnetic member
JP2018109215A
Low magnetic austenite stainless steel and cold rolled steel sheet
JP2018145487A
Austenite stainless steel and method for manufacturing the same
JP2022069229A